2022
DOI: 10.3390/vaccines10060909
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Humoral Immune Response Induced by the Administration of the BNT162b2 Pfizer/BioNTech Vaccine: A Systematic Review

Abstract: The BNT162b2 Pfizer/BioNTech vaccine was the first emergency approved vaccine during the COVID-19 pandemic. The aim of this systematic review was to examine the variations in the humoral immune response induced by the administration of the BNT162b2 vaccine in patients with previous SARS-CoV-2 infection, the elderly, and those with comorbidities and immunosuppression states. Additionally, we analyzed the effect of generated neutralizing antibodies against the new variants of concern of SARS-CoV-2. Pubmed, Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…Regarding previous infection with SARS-CoV-2, a significant relation was found between higher anti-S-RBD IgG titers and a confirmed past infection for both the SpV/SpV and SpV/MOD schemes, with notable, 11-fold higher levels observed for the heterologous scheme. This finding is in accordance with our previously reported values for these vaccination schemes [ 11 ], for the sputnik V homologous scheme [ 20 , 21 ] and for RNAm vaccines [ 23 ].…”
Section: Discussionsupporting
confidence: 94%
“…Regarding previous infection with SARS-CoV-2, a significant relation was found between higher anti-S-RBD IgG titers and a confirmed past infection for both the SpV/SpV and SpV/MOD schemes, with notable, 11-fold higher levels observed for the heterologous scheme. This finding is in accordance with our previously reported values for these vaccination schemes [ 11 ], for the sputnik V homologous scheme [ 20 , 21 ] and for RNAm vaccines [ 23 ].…”
Section: Discussionsupporting
confidence: 94%
“…Lastly, we could not compare test accuracy and optimal thresholds in symptomatic and asymptomatic individuals due to the limited availability of clinical information. As symptomatic infections induce a larger and more persistent humoral response [ 8 ], a higher optimal anti-S IgG threshold could be expected. Test accuracy could hold even for previous BIs that are distant in time.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as age, gender, previous infection before or after vaccination, and the number of doses, may influence anti-S IgG titers in vaccinated subjects. In particular, lower levels were found in elderly individuals, while subjects with previous diagnoses of SARS-CoV-2 infection had a higher titer [ 8 , 9 ]. The time passed after administration is another factor that impacts antibody levels.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published metaanalyses and systematic reviews have analyzed available studies on currently used vaccine regimens. Cortés-Sarabia et al [ 125 ] showed that antibodies developed against the S protein produced by the BNT162b2 vaccine, possessed lower neutralizing activity against the Alpha, Beta, Gamma, and Delta variants of SARS-CoV-2.…”
Section: Immune Response To Sars-cov-2 Vaccinationmentioning
confidence: 99%